Status of Recombinant Factor VIII Concentrate Treatment for Hemophilia A in Italy: Characteristics and Clinical Benefits - Schiavoni, Mario; Napolitano, Mariasanta; Giuffrida, Gaetano; Coluccia, Antonella; Siragusa, Sergio; Calafiore, Valeria; Lassandro, Giuseppe; Giordano, Paola (Frontiers in Medicine, 2019)
The current interest in recombinant factor VIII (rFVIII) products stems from the fact that they offer a technological solution to prolonging the half-life of and reducing the risk of formation of alloantibodies (inhibitors) against FVIII in treated patients with hemophilia A (HA). The Italian health care system has authorized the use of a wide range of rFVIII concentrates of the first, second, and third generation, as well as new innovative rFVIII preparates with an extended half-life (EHL) (Kogenate FS®-Bayer, belonging to the second generation and replaced since 2017 by a product consisting of the same modified molecule; because it is only available until the end of the current year, it will not be considered in this review). Some of these products have unique pharmacodynamic and pharmacokinetic (PK) profiles, including an EHL. The first-generation full-length rFVIII (FL-rFVIII), octocog alfa (Recombinate® Baxter/BIOVIIIx), although the oldest rFVIII product, has several desirable features. Third-generation products include two modified octocog alfa molecules (Advate®, Shire; Kovaltry®, Bayer) as well as the B domain-deleted rFVIII (BDD-rFVIII) moroctocog alfa (ReFacto®-Pfizer). The B domain-truncated (BDT-rFVIII) turoctocog alfa (NovoEight®, Novo Nordisk), the BDD-rFVIII simoctocog alfa (Nuwiq®, Kedrion), the single-chain BDT-rVIII lonoctocog alfa (Afstyla®, CSL Behring), and the BDD-rFVIIIFc efmoroctocog alfa (Elocta®, Sobi-Biogen) are new, innovative products. Simoctocog alfa, because its peculiarities, is considered a fourth-generation rFVIII concentrate. Turoctocog alfa, simoctocog alfa, and lonoctocog alfa have a high affinity for von Willebrand factor (vWF) that reduces renal clearance and prolongs the half-life of rFVIII. Efmoroctocog alfa, a first-in-class rFVIII-Fc fusion protein (rFVIIIFc), has a half-life 1.5–1.8 times longer than that of conventional plasma-derived FVIII (pd-rFVIII) and other rFVIII products. Clinical studies have evaluated the efficacy, safety, and inhibitor development of all these innovative concentrates in both previously treated (PTPs) and untreated patients (PUPs). This review considers the rFVIII products that are indicated for the treatment of patients with severe HA, focusing on those that are commercially available in Italy. Their PK characteristics, immunogenicity, and clinical benefits are discussed and compared.